Emotional intelligence as a mediator between attachment security and empathy in medical students.: Presenter(s): Giulia Rampoldi, University of Mialno - Bicocca, Italy. (April 2023) - Ardenghi, Stefano; Montelisciani, Laura; Antolini, Laura; Donisi, Valeria; Perlini, Cinzia; Rimondini, Michela; Garbin, Davide; Del Piccolo, Lidia; Strepparava, Maria Grazia
Abstract : Background: Although the relationship among Emotional Intelligence (EI), Attachment Security (AS), and Empathy (E) has been previously established, the mechanism through which these three constructs relate to each other is not wholly understood. Since EI has been found to be predicted by AS and to predict E, we advanced an integrated model according to which EI mediates the relation between AS and E in undergraduate medical students. Methods: In a cross-sectional design, the Interpersonal Reactivity Index (IRI), the Emotional Quotient Inventory (EQ-i), the Attachment Style Questionnaire (ASQ), and demographic questions were electronically administrated to 253 second-year medical students (56.13% female) of two medical schools in Northern Italy. Pearson's zero-order correlation coefficients (r) were computed to examine the associations between the three dimensions. To test the indirect effect of AS on E through the variable mediator EI, a mediation analysis was performed using the Structural Equations Modelling (SEM). Findings: As was positively related to the IRI dimensions of Empathic Concern (r=0.17, p=0.008) and Perspective Taking (r=0.24, p<0.001), and negatively to Personal Distress (r=-0.33, p<0.001). Individuals with same levels of AS and higher scores on EQ-i had higher scores (?=0.072, p=0.033) on the empathy latent factor (at the basis of Empathic Concern and Perspective Taking) and lower scores (?=-0.290, p<0.001) on Personal Distress than those with lower EQ-i scores. Discussion: This study shows that EI completely mediated the relationship between AS and empathy dimensions in our study population. Since EI is a dispositional characteristic malleable to modification, this construct should be considered when designing educational interventions and programs to promote medical students' empathy and well-being in interpersonal situations.